Attitude towards science and digital science-related messages in the light of the results of the survey carried out as part of the public consultations in the framework of the CONCISE project - Podgórniak-Krzykacz, Aldona; Wiktorowicz, Justyna (Science Communication in Poland. Participation. Dialogue. Trust, 2021)
The chapter presents a partial analysis of the results of exercises (studies) conducted during the public consultations in the framework of the CONCISE project, which one hundred people attended. They concerned the participants’ general perceptions of science and science-related messages concerning medical issues and climate change published in electronic media. The perception of science was assessed through the prism of the participants’ acceptance of two statements: 1) ‘Science and technology make our lives easier, more comfortable and healthier,’ and 2) ‘Scientific and technological developments can have unforeseen negative side effects that are harmful to human health and the environment.’ Both received high scores, and the support for the statements increased as a result of the discussion among the participants, which indicates that a positive attitude towards science and technology was dominant in the studied group. The participants also put their faith in the capacity of science while expressing a cautious attitude towards its effects. Knowledge about the scale of dissemination in society of the belief about the dangers of scientific advancement allowed us to undertake a public debate and design an information policy on its further development and achievements. The participants assessed digital science news headlines related to medical issues (e-press article and Twitter) and climate change (WhatsApp and Facebook). The conclusions concerned how the subject matter and the format of the headlines impact the way they are received by the participants, convincing them to read the full content of the articles and further disseminate them among friends. These conclusions provide guidelines for science communicators on how to formulate a message addressed to the public to ensure that its dissemination and reception are highly effective.